Dynamic changes in the zone of apposition and diaphragm length during maximal respiratory efforts. - McKenzie, D. K. (1994)
BACKGROUND--Clinical tests of diaphragmatic strength are limited by the wide normal variation in maximal pressure which result, in part, from changes in diaphragmatic length. During relaxation at different lung volumes diaphragmatic length (LDI) can be estimated from the length of the zone of apposition (LZapp) and the transverse diameter of the rib cage (DRC). A study was carried out in two subjects using sequential digital radiography at six frames/second to determine whether these relations apply during maximal respiratory efforts which distort the rib cage and diaphragm. METHODS--The length of the anteroposterior contour of the diaphragm and DRC were determined by curve fitting. LZapp was measured with a millimetre rule. RESULTS--A significant correlation was found between LDI and LZapp during both maximal inspiratory and expulsive manoeuvres (R2 = 0.88 and 0.52). LDI was estimated from the measurements of LZapp and DRC using a multiple regression equation derived from measurements during static relaxation. Despite the complex dynamic events at the onset of these "static" manoeuvres, actual LDI correlated strongly with derived LDI using all data for the two manoeuvres in each subject (R2 = 0.95 and 0.84). Measurements with ultrasonography (12 cm linear probe) and magnetometers confirmed the changes in LZapp and DRC during inspiratory and expulsive efforts. CONCLUSIONS--Non-invasive measurements of LZapp and DRC can be used to derive an accurate estimate of diaphragmatic length under dynamic conditions.